2012
DOI: 10.3390/ijerph9093051
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, Practices and Biomonitoring of Farmers and Residents Exposed to Pesticides in Brazil

Abstract: In this study, the knowledge, attitudes and practices regarding pesticide use and the levels of exposure of farmers and residents to organophosphorous and/or carbamates pesticides were evaluated in two rural settings in Brazil. A questionnaire was completed by 112 farm workers aged ≥18 years. Almost all farmers acknowledged that pesticides were potentially harmful to their health (87.5%); however, over half rarely (48.2%) or never (7.2%) used personal protective devices (PPDs). An association was found (p = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
42
3
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 32 publications
10
42
3
10
Order By: Relevance
“…Our results are different from those of (Juliana et al 2012;Bulgaroni and al. 2012;Joshaghani and al.…”
Section: Mean Values Of Cholinesterase In the Study Populationcontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are different from those of (Juliana et al 2012;Bulgaroni and al. 2012;Joshaghani and al.…”
Section: Mean Values Of Cholinesterase In the Study Populationcontrasting
confidence: 99%
“…We observe that inhibition of enzymatic activity is higher in the majority of the population during the exposure phase (78.95%) than in the non-exposure phase (36.84%) with a significant difference (P = 0.0075). Our findings are consistent with Juliana et al (2012) who found the majority of workers that had ± 30% variation in enzymatic activity during the exposure period. For Fournier et al, (1970), decreases in blood activity of 50 to 70% of exposed individuals can be observed without associated clinical signs.…”
Section: Variation Of the Inhibition Of The Enzymatic Activity Duringsupporting
confidence: 93%
“…Traditionally, chemicals have been used to manage parasites, with an impact on the wellbeing and health of domestic animals, including food-producing livestock (ECOBICHON, 2001;OLIVEIRA PASIANI et al, 2012). However, indiscriminate use of chemical pesticides for veterinary use has driven parasite populations to become resistant to many of them (ANDREOTTI et al, 2011;KAPLAN;VIDYASHANKAR, 2012;CASTRO JANER et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the farmers acknowledged that pesticides were harmful to their health and the environment. Also, farmer's knowledge for pesticide hazards was high, while the reported safety measures were poor [12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%